2002
DOI: 10.1051/parasite/200209117
|View full text |Cite
|
Sign up to set email alerts
|

Hepatozoon kisraen. sp. infecting the lizardAgama stelliois transmitted by the tickHyalommacf.aegyptium

Abstract: Summary :Hepatozoon kisrae n. sp. was found infecting a starred lizard at a site in southeastern Samaria, Palestine. These lizards were also hosts to the ixodid tick Hyolomma cf. aegyptium, which was demonstrated to be the vector of this hemogregarine. Hepatozoon and tick infections occurred in lizards within a very restricted locality; at a second site, nearby, ticks occurred without Hepatozoon infection. Micro-and macromeronts occurred mainly in the lungs, while cyst-like merogonic stages, mainly dizoic, occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 5 publications
3
23
0
1
Order By: Relevance
“…The entire sporogonic development of the dog Hepatozoon (H. americanum), also transmitted by an ixodiid tick (Amblyoma maculatum), appears to occur similarly within the gut cells of its tick host (Mathew et al, 1999). For better insight into the relationship between canine Hepatozoon and Hemolivia, this study, as well as earlier studies on the development of H. canis in its tick host Rhipicephalus sanguineus by Wenyon (1911) and Christophers (1912) (Paperna et al, 2002). Transmission to tortoises is via ingestion of infected ticks.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The entire sporogonic development of the dog Hepatozoon (H. americanum), also transmitted by an ixodiid tick (Amblyoma maculatum), appears to occur similarly within the gut cells of its tick host (Mathew et al, 1999). For better insight into the relationship between canine Hepatozoon and Hemolivia, this study, as well as earlier studies on the development of H. canis in its tick host Rhipicephalus sanguineus by Wenyon (1911) and Christophers (1912) (Paperna et al, 2002). Transmission to tortoises is via ingestion of infected ticks.…”
Section: Discussionmentioning
confidence: 58%
“…The invaginated border of the non-differentiated sporocyst, accompanied on its PV side by numerous round vesicles suggests an absorptive function, whereas this function in H. mariae seems to be fulfilled by the PV border (Smallridge & Paperna, 2000b). The hardening of the mature sporocyst wall is a general phenomenon for all terrestrial-host hemogregarines -Hemolivia as well as Hepatozoon (Paperna et al, 2002), although none of these are challenged to withstand desiccation in the course of their transmission (by the predation of the vector). The sutural slit detected in the H. mauritanicum mature sporocyst wall has not yet been seen in the other species.…”
Section: Discussionmentioning
confidence: 99%
“…Monozoic cysts have been recorded for H. griseisciuri of squirrels (Desser 1990); both monozoic and dizoic for H. balfouri of jerboas (Hoogstraal 1961); dizoic for H. sauromali of the iguanid lizard Sauromalus hispidus (Lewis & Wagner 1964), monozoic to hexazoic for H. domerguei (Landau et al 1972) and H. caimani (present investigation), and dizoic to octozoic for H. kisrae of the lizard Agama stellio (Paperna et al 2002). Cysts containing four or more cystozoites may present problems in their differentiation from mature, primary schizonts, which are of similar size.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that a variety of haematophagous arthropods can serve as vectors, for the full sporogony of Hepatozoon spp. has been recorded in experimental or natural infections of C. fatigans, C. tarsalis, C. pipiens and C. territans (Mackerras 1962, Booden et al 1970, Bashtar et al 1984, Desser et al 1995, Aedes togoi and Aedes aegypti (Ball et al 1969, Lowichik et al 1993, Anopheles stephensi (Landau et al 1972), the ticks Argas brumpti and Hyalomma aegyptium (Garnham 1955, Paperna et al 2002, triatomid bugs (Da Rocha e Silva 1975), a sand fly, Lutzomyia sp. (Lainson, unpublished observation) and the tsetse fly, Glossina palpalis (Hoare 1932).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of authors reported on two types of meronts in Hepatozoon, usually called macro-and micromeronts, or Y meronts and X meronts, respectively (i.a. Smith 1996, Telford et al 2001, Paperna et al 2002. So far, no species of Hemolivia have been reported to share this trait (Michel 1973, Petit et al 1990, Paperna and Smallridge 2001).…”
Section: Discussionmentioning
confidence: 99%